PENGEMBANGAN ASESMEN PORTOFOLIO BERBASIS SDGs UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS V PADA MATERI EKOSISTEM - Dwi Andriani, Dini; Hamdu, Ghullam; Ramadhani Putri, Agnestasia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Creative thinking is an important skill that can be taught in elementary school. The application of assessment is a key element in the learning process which is related to achieving student learning outcomes and plays a role in developing these skills. So this research aims to develop an SDGs-based portfolio assessment to improve creative thinking skills in the Ecosystem material for fifth grade elementary school students. The model used in research using the Design Based Research (DBR) research model consists of four stages, namely the Identification and Analysis of Needs stage, the design stage, the Trial or Implementation stage, and Reflection. Data collection techniques include interviews, documentation studies, expert validation sheets and student and teacher questionnaires. The results of the expert assessment validation test obtained a score of 83.3%, the learning tool expert validation obtained a score of 85.7% so it was categorized as